Bliski Wschód w polityce zagranicznej Chin w erze Xi Jinpinga: Znaczenie kultury strategicznej (Politeja, 2025)
THE MIDDLE EAST IN CHINA’S FOREIGN POLICY IN THE XI JINPING ERA: THE IMPORTANCE OF STRATEGIC CULTUREThe article puts forward a hypothesis according to which cooperation with Middle Eastern countries is primarily intended to ensure China the status of a superpower in the international system. The theory of neoclassical realism was chosen as the theoretical basis, and strategic culture was chosen as the intervening variable. Based on Charles Kupchan’s concepts, six images were identified in China’s contemporary strategic culture. In this light, China creates a broadly understood alternative for Middle Eastern countries and pursues its interests. Thanks to cooperation with Middle Eastern countries, the PRC is gaining significant support, its position in the UN is strengthening, and initiatives such as the March 2023 mediation are increasing prestige. At the same time, they have access to the necessary natural resources and stable cooperation with Arab countries and Iran in the region, and their military importance is gradually increasing. China can give Middle Eastern countries what the US cannot – anything to climb and gain the same importance as their biggest rival.